2020
DOI: 10.21203/rs.2.22633/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Performance of the Upper Limb Module—A Reliable and Valid Evaluation for Chinese Patients with Duchenne Muscular Dystrophy

Abstract: Background Duchenne muscular dystrophy is a genetic disease leading to progressive muscle weakness and degeneration. Effective assessment tool is needed to allow monitoring of progress to guide the management. This study assessed the reliability and validity of the Performance of Upper Limb (PUL) Module when used in patients with Duchenne Muscular Dystrophy (DMD). MethodsTotal thirty-three Chinese DMD patients were included. Twenty-five video-recorded PUL Module version 1.3 assessments were performed for the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The instruments with the highest number of measurement properties tested were the MFM scale and PUL. 35,49,[66][67][68][69][70][71][72][73][74] In most instruments, measurement properties were classified as sufficient according to the criterion of good measurement. Content validity, reliability, structural validity, and hypothesis testing for construct validity were the properties that met the least quality criteria.…”
Section: Summary Of the Studies Included In The Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The instruments with the highest number of measurement properties tested were the MFM scale and PUL. 35,49,[66][67][68][69][70][71][72][73][74] In most instruments, measurement properties were classified as sufficient according to the criterion of good measurement. Content validity, reliability, structural validity, and hypothesis testing for construct validity were the properties that met the least quality criteria.…”
Section: Summary Of the Studies Included In The Reviewmentioning
confidence: 99%
“…16,35,44,47,53,54,63,65,67,69,70 Hypothesis testing for construct and content validity was evaluated in seven instruments and structural validity was evaluated in six. 16,35,44,[47][48][49]53,54,57,63,69,[70][71][72] Responsiveness was measured in only three instruments 50,52,73,74 and examination of criterion validity was made in only two. 67,69 Measurement error was reported in only one instrument 69 and none of the five studies that translated and carried out cross-cultural adaptation of the instruments reported crosscultural validity and/or measurement invariance.…”
Section: Summary Of the Studies Included In The Reviewmentioning
confidence: 99%
See 3 more Smart Citations